2015
DOI: 10.1093/ckj/sfv094
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of amitriptyline intoxications by extended high cut-off dialysis

Abstract: Antidepressants, especially amitriptyline, are among the most frequent drug classes involved in intoxications. Despite its small molecular weight, amitriptyline is not considered to be eliminated by extracorporeal treatment methods due to its high protein binding and large volume of distribution. New high cut-off dialysers have so far not been used for removal of amitriptyline. We report two cases of amitriptyline poisoning in which we measured the amitriptyline elimination using extended high cut-off (HCO) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…In patients with life threatening amitriptyline intoxication successful results had been reported with plasma exchange had been (7,(18)(19)(20)(21). Recently one study reported successful result with extended high cut-off dialysis (9). In our case, we performed selective plasma exchange due to the persisting life threatening clinical condition despite all other treatment options.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In patients with life threatening amitriptyline intoxication successful results had been reported with plasma exchange had been (7,(18)(19)(20)(21). Recently one study reported successful result with extended high cut-off dialysis (9). In our case, we performed selective plasma exchange due to the persisting life threatening clinical condition despite all other treatment options.…”
Section: Discussionmentioning
confidence: 78%
“…Amitriptylin is one of the most common used antidepressants. Also the tricyclic antidepressants, especially the amitryptiline, are the most common used drugs in drug intoxication worldwide (8,9). Acute results of amitriptyline intoxication had been well defined both in children and adults (1, 3, 4, 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECTR is unlikely to be useful for such toxins because of their large volume of distribution, which limits their extracorporeal removal, and availability of alternative treatments. However, some clinicians still consider that ECTR may be indicated for some nonclassic toxins like tricyclic antidepressants (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The found cases were divided into three groups with corresponding methodology: Cases without ingested dose reported [ 35 , 43 ]: the free cardiac AT and NT concentrations were estimated based on observed plasma AT and NT concentrations according to the (Eq. 5 ): where C free,cardiac is drug free cardiac concentration, Kp ht is heart tissue to plasma partition coefficient, and fu ht is drug unbound fraction in heart tissue.…”
Section: Methodsmentioning
confidence: 99%